Aging of running shoes and its effect on mechanical and biomechanical variables: implications for runners - Chambon, N.; Sevrez, V.; Ly, Q. H.; Guéguen, N.; Berton, E.; Rao, G. (Journal of Sports Sciences, 2014)
This study investigates the effect of running shoes` aging on mechanical and biomechanical parameters as a function of midsole materials (viscous, intermediate, elastic) and ground inclination. To this aim, heel area of the shoe (under calcaneal tuberosity) was first mechanically aged at realistic frequency and impact magnitudes based on a 660 km training plan. Stiffness (ST) and viscosity were then measured on both aged and matching new shoes, and repercussions on biomechanical variables (joint kinematics, muscular pre-activation, vertical ground reaction force and tibial acceleration) were assessed during a leg-extended stepping-down task designed to mimic the characteristics of running impacts. Shoes` aging led to increased ST (means: from 127 to 154 N/mm) and decreased energy dissipation (viscosity) (means: from 2.19 to 1.88 J). The effects induced by mechanical changes on body kinematics were very small. However, they led with the elastic shoe to increased vastus lateralis pre-activation, tibial acceleration peak (means: from 4.5 g to 5.2 g) and rate. Among the three shoes tested, the shoe with intermediate midsole foam provided the best compromise between viscosity and elasticity. The optimum balance remains to be found for the design of shoes regarding at once cushioning, durability and injury prevention.